Persepsi Masyarakat Muslim terhadap Praktik Pembiayaan Bank Titil - Mochammad Andrean Hadi Ananda; Mahfiyah Mahfiyah; Miftakhul Jannah (Universitas Islam Raden Rahmat, 2026)
This study aims to understand the muslim community's perception of Bank Titil's financing practices in Jatiagung Village, Gumukmas Subdistrict, as a response to urgent financial needs. Using a qualitative approach and in-depth interviews, this study involved community members who use Bank Titil's services to explore their views and experiences. Findings indicate that while the community values the ease and speed of the loan process, they also expressed concerns about the high interest rates that can be burdensome. Factors influencing the Jatiagung community's decision to borrow from Bank Titil include economic factors, ease of access, and their low level of financial literacy, particularly regarding Islamic financial literacy. The implications of this study are important for the government to provide easy financial access to legal and Islamic financial institutions for the village community and provide education related to Islamic financial literacy. This is to ensure that the community maintains Islamic values in conducting economic activities.